Absorption of volatile organic compounds (VOCs) by polymer tubing: implications for indoor air and use as a simple gas-phase volatility separation technique - M. A. Morris; D. Pagonis; D. Pagonis; D. A. Day; J. A. de Gouw; P. J. Ziemann; J. L. Jimenez (Atmospheric Measurement Techniques, 2024)
Previous studies have demonstrated volatility-dependent absorption of gas-phase volatile organic compounds (VOCs) to Teflon and other polymers. Polymer–VOC interactions are relevant for atmospheric chemistry sampling, as gas–wall partitioning in polymer tubing can cause delays and biases during measurements. They are also relevant to the study of indoor chemistry, where polymer-based materials are abundant (e.g., carpets and paints). In this work, we quantify the absorptive capacities of multiple tubing materials, including four nonconductive polymers (important for gas sampling and indoor air quality), four electrically conductive polymers and two commercial steel coatings (for gas and particle sampling). We compare their performance to previously characterized materials. To quantify the absorptive capacities, we expose the tubing to a series of ketones in the volatility range 104–109 µg m−3 and monitor transmission. For slow-diffusion polymers (e.g., perfluoroalkoxy alkane (PFA) Teflon and nylon), absorption is limited to a thin surface layer, and a single-layer absorption model can fit the data well. For fast-diffusion polymers (e.g., polyethylene and conductive silicone), a larger depth of the polymer is available for diffusion, and a multilayer absorption model is needed. The multilayer model allows fitting solid-phase diffusion coefficients for different materials, which range from 4×10-9<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="ade54f6758830c31105050816cdb4782"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-17-1545-2024-ie00001.svg" width="42pt" height="14pt" src="amt-17-1545-2024-ie00001.png"/></svg:svg> to 4×10-7<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="b49dd19f655a2b3c0f8859ffac9f534c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-17-1545-2024-ie00002.svg" width="42pt" height="13pt" src="amt-17-1545-2024-ie00002.png"/></svg:svg> cm2 s−1. These diffusion coefficients are ∼ 8 orders of magnitude larger than literature values for fluorinated ethylene propylene (FEP) Teflon film. This enormous difference explains the differences in VOC absorption measured here. We fit an equivalent absorptive mass (CW, µg m−3) for each absorptive material. We found PFA to be the least absorptive, with CW ∼ 105 µg m−3, and conductive silicone to be the most absorptive, with CW ∼ 1013 µg m−3. PFA transmits VOCs easily and intermediate-volatility species (IVOCs) with quantifiable delays. In contrast, conductive silicone tubing transmits only the most volatile VOCs, denuding all lower-volatility species. Semi-volatile species (SVOCs) are very difficult to sample quantitatively through any tubing material. We demonstrate a system combining several slow- and fast-diffusion tubing materials that can be used to separate a mixture of VOCs into volatility classes. New conductive silicone tubing contaminated the gas stream with siloxanes, but this effect was reduced 10 000-fold for aged tubing, while maintaining the same absorptive properties. SilcoNert (tested in this work) and Silonite (tested in previous work) steel coatings showed gas transmission that was almost as good as PFA, but since they undergo adsorption, their delay times may be humidity- and concentration-dependent.